Preface-PIRC 2024 - POSTGRADUATE; INDUSTRY RESEARCH COLLOQUIUM 2024 (PIRC),FACAULTY OF ENGINEERING; BUILT ENVIRONMENT (Semarak Proceedings of Natural and Environmental Sciences, 2025)
POSTGRADUATE AND INDUSTRY RESEARCH COLLOQUIUM 2024